Utilization of School Library, Learning Strategy, Motivation as Intervening Towards Students’ Learning Achievement - Wardana, Isti Maryani; Prihatin, Titi; Purwanti, Eko (Journal of Primary Education)
The objective of this study is to analyze the effect of the use of school libraries and learning strategies towards students’ achievement with learning motivation as an intervening. This Research Method was a quantitative correlation implemented towards V graders students of Public Primary School in Gunungpati District Semarang City through questionnaire, documentation, and observation. The use of school libraries and learning strategies as an independent variable, students’ achievement as a dependent variable and learning motivation as an intervening variable, were analyzed using path analysis by using t test and Sobel test. The results of the study show that the utilization of the library is relatively sufficient, so that students’ achievement becomes less optimal (p = 0.032 < 0.05). Teachers' learning strategies are sufficient and have a direct effect on less optimal learning achievement (p = 0.000 < 0.05). Learning motivation has an effect as an intervening effect of the utilization of a library towards learning achievements (p = 0.031 < 0.05). The conclusion of this study is the utilization of library and learning strategies have an effect towards learning achievement with learning motivation as an intervening variable towards                         V graders students of Public Primary School in Gunungpati District.